2006
DOI: 10.1111/j.1440-1843.2006.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of circulating KL‐6 in idiopathic pulmonary fibrosis

Abstract: These results suggest that initial evaluation of serum KL-6 level can predict survival in patients with IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
176
7
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(196 citation statements)
references
References 28 publications
10
176
7
3
Order By: Relevance
“…Satoh et al reported an increased mortality in patients with an IIP, including patients with IPF, with serum levels of KL-6 > 1000 U/ml at initial measurement [33]. Furthermore, Yokoyama et al reported worse survival of IPF patients with KL-6 levels > 1000U/ml at time of presentation, in a retrospective study of a total of 27 patients [34]. Elevates KL-6 levels have also been associated with NSIP.…”
Section: Kl-6mentioning
confidence: 99%
“…Satoh et al reported an increased mortality in patients with an IIP, including patients with IPF, with serum levels of KL-6 > 1000 U/ml at initial measurement [33]. Furthermore, Yokoyama et al reported worse survival of IPF patients with KL-6 levels > 1000U/ml at time of presentation, in a retrospective study of a total of 27 patients [34]. Elevates KL-6 levels have also been associated with NSIP.…”
Section: Kl-6mentioning
confidence: 99%
“…Elevated serum levels of KL-6, and especially levels over 1,000 U/mL, upon initial measurement are reported to be related to increased mortality (17). The progression of IPF is significantly faster in patients with KL-6 levels of 1,000 U/mL or higher upon initial measurement than in patients with KL-6 levels below 1,000 U/mL (18).…”
Section: Kl-6mentioning
confidence: 99%
“…Elevated levels of serum KL-6 have been found in patients with clinically confirmed progression [33] and have been associated with increased mortality risk [36,37].…”
Section: Table 2 Candidate Biomarkers For Idiopathic Pulmonary Fibrosmentioning
confidence: 99%